Ulrich Beck and Japan. (December 2015) - Abe, Kiyoshi
Looking back, the process in which Ulrich Beck's epoch-making work of Risikogesellschaft was introduced and translated into Japanese attracted great public interest there. This paper revisits the significance of the concept 'risk society' in the context of postwar Japan. Facing both the natural and artificial disasters caused by the huge earthquake in Fukushima in 2011, Japanese society was compelled to reconsider its atomic energy policy implemented after the end of the Second World War. While the general public has strongly embraced an anti-nuclear sentiment after witnessing the 3/11 disasters, the government and leading LDP are still eager to restart the atomic plants that have been suspended since the tragedy in Fukushima. Considering those complicated sociopolitical conditions concerning the legitimacy of the atomic energy policy in Japan, Risikogesellschaft redux might be a useful way through which we can envisage a future direction to take.